Profile of Skills Students in Resolving Problems Trigonometry Based on Personality Type Myer-Briggs - Anggreini , Dewi; Saputra, Daffit Krisna (Proceeding International Conference on Science and Engineering, 2020)
The problem in this study is the low ability of students to solve problems. That is because students only refer to the examples of questions given by the teacher so that students have difficulty if given questions that are not the same as the examples given by the teacher. Diverse problem solving solutions are needed because students still find difficult to draw conclusions from the questions they have worked on. The purpose of this study is to describe students' ability to solve trigonometric problems in terms of the personality type of Myer-Briggs, namely ISTJ, ESFJ, ESTP, INFJ, ISTJ, ISTP, ESTJ, INTP and ISFJ. This research is a type of descriptive research using a qualitative approach. Methods of data collection using the MBTI questionnaire, math problem solving ability test questions and interviews. The results showed that the ISTJ personality type fulfilled 4 indicators of problem solving very well, while the personality types of ESFJ, ESTP, INFJ, ISTJ, ISTP, and ESTJ met 4 indicators of problem solving well, and for personality types ENTJ, INTP, and ISFJ were sufficient good by meeting 3 of the 4 indicators of problem solving. The results of the study can be used to improve students' mathematical problem solving abilities by further enhancing the positive characteristics present in students. Can inspire students to better understand the type of personality they have in themselves and hone their abilities to be more improved.